Penilaian tingkat pencemaran logam berat dalam sedimen di perairan Pulau Morotai, Maluku Utara - Edward . (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2015)
Abstract. Morotai Waters, located in North of Maluku, has panoramic coastal waters and marine natural beautiful view, and rich of fishery resources, so it is potentially to be developed as a location for recreation area, mariculture, and fisheries industries. For those reasons, the development need a lot of base data, one of the data base is heavy metals. Heavy metals comes from various human activities, both on land and at sea and geological process. Heavy metals in low levels needed by aquatic organisms for the growth and development of its life, but high levels are toxic. Measurement of levels of heavy metals Pb, Cd, Cu, Zn, Ni, and Cr in the sediment in the waters of Morotai was conducted in June 2005. Sediment samples is taken using gravity cores at 13 research stations. The levels of heavy metals were measured using Atomic Absorption Spectrophotometer (AAS). The purpose of this study was to evaluate the contamination and pollution of heavy metals pollution level in Morotai Island waters using CF, I_geo, and PLI. The results of this study show that, based on the value of contamination factors (CF), geoaccumulation indices (I_geo) and pollution load indices (PLI), sediment in this water is include to uncontamination and unpolluted category and is still safe for marine life (CF0, I_geo0 and PLI 1).Keywords: Morotai; sediment; heavy metal; pollutionsAbstrak. Perairan Morotai terletak di Maluku Utara, perairan ini memiliki panorama pantai dan alam laut yang indah, serta kaya akan sumberdaya perikanan, sehingga berpotensi untuk dikembangkan sebagai lokasi wisata bahari, budidaya, dan industri perikanan. Untuk pengembangan tersebut diperlukan data dasar, salah satu data dasar tersebut adalah data logam berat. Logam berat berasal dari berbagai aktivitas manusia yang ada di darat maupun di laut, dan proses geologis di alam. Logam berat dalam kadar yang rendah diperlukan oleh organisme perairan untuk pertumbuhan dan perkembangan hidupnya, namun dalam kadar yang tinggi bersifat racun. Pengukuran kadar logam berat Pb, Cd, Cu, Zn, Ni, dan Cr dalam sedimen di perairan Morotai telah dilakukan pada bulan Juni 2005. Contoh sedimen diambil dengan menggunakan gravity core pada 13 stasiun penelitian. Kadar logam berat diukur dengan menggunakan Spektrofotometer Serapan Atom (SSA). Tujuan penelitian ini adalah untuk menilai tingkat kontaminasi dan tingkat pencemaran logam berat dalam sedimen di perairan Pulau Morotai dengan menggunakan nilai faktor kontaminasi (CF), indeks geoakumulasi (I_geo) dan indeks beban pencemaran (PLI). Hasilnya menunjukkan berdasarkan nilai CF, I_geo, dan PLI, sedimen di perairan ini termasuk kategori tidak terkontaminasi dan tidak tercemar oleh logam berat Pb, Cd, Cu, Zn, Ni, dan Cr, serta masih aman untuk kehidupan biota laut (CF0, I_geo0 dan PLI1).Kata Kunci: Morotai; sedimen; logam berat; pencemaran